KENDALA GURU DALAM MENGAJARKAN MEMBACA PEMAHAMAN PADA SISWA KELAS TINGGI DENGAN MINAT BACA RENDAH DI SD NEGERI 187/I TERATAI - Maulidia Alqanita; Deva Merlin Claudia; Cahya Karinna; Khoirunnisa; Silvina Noviyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the obstacles faced by teachers in teaching reading comprehension to upper-grade elementary school students with low reading interest at SD Negeri 187/I Teratai. This research employed a descriptive qualitative approach through observation and interviews with the fourth-grade teacher, Nursaadatul Fitri. The findings show that the teacher encountered several main challenges, including students’ lack of focus during lessons, passive participation in listening activities, unfamiliarity with reading seriously, and low reading interest. In the teaching process, the teacher used several strategies, such as oral reading, alternating reading, individual reading, rewriting the content of texts, and presenting the written results again to help students understand the reading material. The learning media used included textbooks, storybooks, photocopied materials, and reading resources from the school library. The findings also indicate that students’ low reading interest is influenced by home habits, parental attention, the surrounding environment, and the use of mobile devices. Although the teacher’s efforts have helped improve students’ reading comprehension, the results have not yet been optimal because reading achievement depends not only on the teacher, but also on family support and consistent reading habits.